N-gonal Truncated Pyramids.

Geometry Level pending

In the diagram above, a sphere is inscribed in a n n -gonal truncated pyramid such that the volume of the n n -gonal truncated pyramid is twice the volume of the sphere.

Let θ ( n ) \theta(n) be the slant height angle of the n n -gonal truncated pyramid.

Find lim n θ ( n ) \lim_{n \rightarrow \infty} \theta(n) in degrees.

Note: My intention is to use the n n -gonal truncated pyramid not a truncated cone.


The answer is 63.43494882.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
Feb 10, 2020

A B C D B E x H = y H H ( x y ) H = x H H = x H x y \triangle{ABC} \sim \triangle{DBE} \implies \dfrac{x}{H^{*}} = \dfrac{y}{H^{*} - H} \implies (x - y)H^{*} = xH \implies H^{*} = \dfrac{xH}{x - y}

\implies

Volume of truncated pyramid V T ( n ) = n 12 cot ( π n ) ( x 2 ( x H x y ) y 2 ( x H x y H ) ) = V_{T}(n) = \dfrac{n}{12}\cot(\dfrac{\pi}{n})(x^2(\dfrac{xH}{x - y}) - y^2(\dfrac{xH}{x - y} - H)) =

n 12 cot ( π n ) ( x 3 x y 2 + x y 2 y 3 x y ) H = \dfrac{n}{12}\cot(\dfrac{\pi}{n})(\dfrac{x^3 - xy^2 + xy^2 - y^3}{x - y})H = n 12 cot ( π n ) ( x 2 + x y + y 2 ) H \dfrac{n}{12}\cot(\dfrac{\pi}{n})(x^2 + xy + y^2)H .

Using the fact that tangents to a circle from an outside point are congruent we obtain the diagram above.

The height H H of the truncated cone is H = 2 r H = 2r

Using right A B C \triangle{ABC} we have:

( w + m ) 2 = ( w m ) 2 + 4 r 2 w 2 + 2 w m + m 2 = w 2 2 w m + m 2 + 4 r 2 4 w m = 4 r 2 r 2 = w m (w + m)^2 = (w - m)^2 + 4r^2 \implies w^2 + 2wm + m^2 = w^2 - 2wm + m^2 + 4r^2 \implies 4wm = 4r^2 \implies r^2 = wm \implies

r = w m r = \sqrt{wm} .

The volume of the inscribed sphere V s ( n ) = 4 3 π ( w m ) 3 2 V_{s}(n) = \dfrac{4}{3}\pi(wm)^{\frac{3}{2}} .

The volume of the truncated n n - gonal pyramid is:

V T ( n ) = 2 n 3 tan ( π n ) ( w 2 + w m + m 2 ) ( w m ) 1 2 V_{T}(n) = \dfrac{2n}{3}\tan(\dfrac{\pi}{n})(w^2 + wm + m^2)(wm)^{\frac{1}{2}}

V T ( n ) = 2 V s ( n ) w 2 + w m + m 2 = 4 π n cot ( π n ) w m V_{T}(n) = 2V_{s}(n) \implies w^2 + wm + m^2 = \dfrac{4\pi}{n}\cot(\dfrac{\pi}{n})wm \implies

w 2 ( 4 π n cot ( π n ) 1 ) w m + m 2 = 0 w^2 - (\dfrac{4\pi}{n}\cot(\dfrac{\pi}{n}) - 1)wm + m^2 = 0

For n 3 : n \geq 3 :

Let s ( n ) = 4 π n cot ( π n ) 1 s(n) = \dfrac{4\pi}{n}\cot(\dfrac{\pi}{n}) - 1

( 0 < s ( n ) < 3 ) (0 < s(n) < 3) and s ( n ) s(n) is monotonic increasing for n 3 n \geq 3 and lim n s ( n ) = 3 \lim_{n \rightarrow \infty} s(n ) = 3

To show: lim n s ( n ) = 3 \lim_{n \rightarrow \infty} s(n ) = 3

To show: lim n n sin ( π n ) = π \lim_{n \rightarrow \infty} n\sin(\dfrac{\pi}{n}) = \pi

Using the inequality: cos ( u ) < sin ( u ) u < 1 \cos(u) < \dfrac{\sin(u)}{u} < 1 \implies cos ( π n ) < sin ( π n ) π n < 1 \cos(\dfrac{\pi}{n} ) < \dfrac{\sin(\dfrac{\pi}{n})}{\dfrac{\pi}{n} } < 1 \implies

π cos ( π n ) < n sin ( π n ) < π \pi\cos(\dfrac{\pi}{n}) < n\sin(\dfrac{\pi}{n}) < \pi and π lim n cos ( π n ) = π lim n n sin ( π n ) = π \pi\lim_{n \rightarrow \infty} \cos(\dfrac{\pi}{n}) = \pi \implies \lim_{n \rightarrow \infty} n\sin(\dfrac{\pi}{n}) = \pi

\implies

4 π lim n cot ( π n ) n = 4\pi\lim_{n \rightarrow \infty} \dfrac{\cot(\dfrac{\pi}{n})}{n} = 4 π 2 lim n csc 2 ( π n ) n 2 = 4\pi^2\lim_{n \rightarrow \infty} \dfrac{\csc^2(\dfrac{\pi}{n})}{n^2} =

4 π 2 lim n 1 ( n sin ( π n ) ) 2 = 4 π 2 ( 1 π 2 ) = 4 4\pi^2\lim_{n \rightarrow \infty} \dfrac{1}{(n\sin(\dfrac{\pi}{n}))^2} = 4\pi^2(\dfrac{1}{\pi^2}) = 4

lim n s ( n ) = 3 \implies \lim_{n \rightarrow \infty} s(n) = 3 .

w 2 ( 4 π n cot ( π n ) 1 ) w m + m 2 = 0 w^2 - (\dfrac{4\pi}{n}\cot(\dfrac{\pi}{n}) - 1)wm + m^2 = 0 \implies

w ( n ) = ( 4 π n cot ( π n ) 1 ± ( 4 π n cot ( π n ) 1 ) 2 4 2 ) m w(n) = (\dfrac{\dfrac{4\pi}{n}\cot(\dfrac{\pi}{n}) - 1 \pm \sqrt{(\dfrac{4\pi}{n}\cot(\dfrac{\pi}{n}) - 1)^2 - 4}}{2})m = ( s ( n ) ± s ( n ) 2 4 2 ) m = (\dfrac{s(n) \pm \sqrt{s(n)^2 - 4}}{2})m

w 1 ( n ) m = s ( n ) s ( n ) 2 4 2 < 3 5 2 < 1 \dfrac{w_{1}(n)}{m} = \dfrac{s(n) - \sqrt{s(n)^2 - 4}}{2} < \dfrac{3 - \sqrt{5}}{2} < 1

and

w 2 ( n ) m = s ( n ) + s ( n ) 2 4 2 > 3 + 5 2 > 1 \dfrac{w_{2}(n)}{m} = \dfrac{s(n) + \sqrt{s(n)^2 - 4}}{2} > \dfrac{3 + \sqrt{5}}{2} > 1

Since w m > 1 \dfrac{w}{m} > 1 we choose w ( n ) = w 2 ( n ) = ( s ( n ) + s ( n ) 2 4 2 ) m w(n) = w_{2}(n) = (\dfrac{s(n) + \sqrt{s(n)^2 - 4}}{2})m

lim n w ( n ) = 3 + 5 2 m \implies \lim_{n \rightarrow \infty} w(n) = \dfrac{3 + \sqrt{5}}{2}m

Let cos ( θ ( n ) ) = w ( n ) 1 w ( n ) + 1 \cos(\theta(n)) = \dfrac{w(n) - 1}{w(n) + 1}

lim n w ( n ) m w ( n ) + m = 1 + 5 5 + 5 \implies \lim_{n \rightarrow \infty} \dfrac{w(n) - m}{w(n) + m} = \dfrac{1 + \sqrt{5}}{5 + \sqrt{5}} = 1 5 = cos ( θ ) = \dfrac{1}{\sqrt{5}} = \cos(\theta)

θ = 63.43494882 \implies \theta = \boxed{63.43494882} .

For a truncated cone, this angle is 57.46577 ° 57.46577\degree . Why is the difference?

A Former Brilliant Member - 1 year, 4 months ago

Log in to reply

I recently did a problem where a sphere is inscribed in a truncated cone such that the volume of the truncated cone is twice the volume of the sphere.

You were asked to find the measure of the slant height angle(in degrees) and the measure of the angle is the same, I.E; 63.4349488 2 63.43494882^{\circ} .

My solution is below:

Using the fact that tangents to a circle from an outside point are congruent we obtain the diagram above.

The height h h of the truncated cone is h = 2 r h = 2r

Using right A B C \triangle{ABC} we have:

( w + m ) 2 = ( w m ) 2 + 4 r 2 w 2 + 2 w m + m 2 = w 2 2 w m + m 2 + 4 r 2 4 w m = 4 r 2 r 2 = w m (w + m)^2 = (w - m)^2 + 4r^2 \implies w^2 + 2wm + m^2 = w^2 - 2wm + m^2 + 4r^2 \implies 4wm = 4r^2 \implies r^2 = wm \implies

r = w m r = \sqrt{wm} .

The volume of the inscribed sphere V s = 4 3 π ( w m ) 3 2 V_{s} = \dfrac{4}{3}\pi(wm)^{\frac{3}{2}}

and

The volume of the truncated cone is V T = 2 π 3 ( w 2 + w m + m 2 ) ( w m ) 1 2 V_{T} = \dfrac{2\pi}{3}(w^2 + wm + m^2)(wm)^{\frac{1}{2}}

V T = 2 V s w 2 + w m + m 2 = 4 w m w 2 3 w m + m 2 = 0 V_{T} = 2V_{s} \implies w^2 + wm + m^2 = 4wm \implies w^2 - 3wm + m^2 = 0 \implies w = ( 3 ± 5 2 ) m w = (\dfrac{3 \pm \sqrt{5}}{2})m

Since w m > 1 \dfrac{w}{m} > 1 we choose w = ( 3 + 5 2 ) m cos ( θ ) = w = (\dfrac{3 + \sqrt{5}}{2})m \implies \cos(\theta) = w m w + m = 1 + 5 5 + 5 = 1 5 \dfrac{w - m}{w + m} = \dfrac{1 + \sqrt{5}}{5 + \sqrt{5}} = \dfrac{1}{\sqrt{5}}

θ 63.4349488 2 \implies \theta \approx \boxed{63.43494882^{\circ}} .

Rocco Dalto - 1 year, 4 months ago

Log in to reply

OK, thanks.

A Former Brilliant Member - 1 year, 4 months ago

Log in to reply

@A Former Brilliant Member No problem.

Rocco Dalto - 1 year, 4 months ago

Log in to reply

@Rocco Dalto Keep continuing the series. It's interesting. :)

A Former Brilliant Member - 1 year, 4 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...